Nansen in the frozen world [electronic resource] - Read, John E. (John Elliot), b. 1845. A brief history of the principal earlier Arctic explorations from the ninth century to the Peary expedition.; Nansen, Fridtjof, 1861-1930.; Berens, S. L.; Astrup, Eivind, 1871-1895. Peary's journey across northern Greenland. (Chicago : Waverly, 1897)
At head of title: The "Fram" expedition. "Preceded by a biography of the great explorer and copious extracts from Nansen's 'First crossing of Greenland', also an account by Eivind Astrup of life among people near the pole, and his Journey across northern Greenland with lieut. R.E. Peary, U.S.N. .followed by a brief history of the principal earlier arctic explorations from the ninth century to the Peary expedition, including those of Cabot, Frobisher, Bering, Sir John Franklin, Kane, Hayes, Hall, Nordenskjold, Nares, Schwatka, DeLong, Greely, and others, by John E. Read." Electronic reproduction. Mode of access: Internet. 44